2021
DOI: 10.1099/mic.0.001086
|View full text |Cite
|
Sign up to set email alerts
|

The dilution effect limits plasmid horizontal transmission in multispecies bacterial communities

Abstract: By transferring ecologically important traits between species, plasmids drive genomic divergence and evolutionary innovation in their bacterial hosts. Bacterial communities are often diverse and contain multiple coexisting plasmids, but the dynamics of plasmids in multi-species communities are poorly understood. Here, we show, using experimental multi-species communities containing two plasmids, that bacterial diversity limits the horizontal transmission of plasmids due to the ‘dilution effect’; this is an epi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In turn, plasmid maintenance is decreased in communities with low conjugation frequencies, where interspecific competition can increase the cost of plasmid carriage. That said, recent work indicates that community context can also limit conjugation to focal species due to the dilution effect [23].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, plasmid maintenance is decreased in communities with low conjugation frequencies, where interspecific competition can increase the cost of plasmid carriage. That said, recent work indicates that community context can also limit conjugation to focal species due to the dilution effect [23].…”
Section: Discussionmentioning
confidence: 99%
“…Diverse multispecies communities will contain a diversity of possible hosts, each of which will vary in their ability to harbour and spread conjugative plasmids [43] ; less-permissive hosts with low conjugation rates will introduce barriers to the infectious spread of conjugative plasmids within the community and may ultimately destabilise the maintenance of purely infectious plasmids. An elegant study by Kottara et al [44] demonstrated this effect within communities, establishing that the dilution effect — a hypothesis in disease ecology [45] whereby disease risk is reduced as a result of less efficient disease vectors diluting the impact of highly competent vectors — can equally apply to the infectious spread of plasmids. Through tracking the spread of a highly conjugative plasmid, pQBR57, within multispecies communities, it was shown that the presence of a less permissive host with significantly lower conjugation rates reduced the overall infectivity of the plasmid within the focal species [44] .…”
Section: Factors Limiting Plasmid Transfer and Persistence Within Mic...mentioning
confidence: 99%
“…In this paper, we have highlighted the possibility that the rate of conjugation may change (substantially) with the identity of the plasmid-bearing cell [32][33][34]. For example, as a plasmid moves from the original donor strain to the recipient background (forming a transconjugant), the transfer rate can change (i.e., γ D 6 ¼ γ T ).…”
Section: The Ldm Approach Is Broadly Applicablementioning
confidence: 99%